The fixed image in cinema as a potential altered vision strategy (AN-ICON. Studies in Environmental Images [ISSN 2785-7433], 2022)
The article intends to propose some analyses of a possible formal occurrence of “altered states” in cinema: the stopping of the flow of the cinematographic image in a still image. Through some theoretical references (Metz, Bazin, Lyotard, Deleuze, Bellour, Barthes, Montani) I will try to understand if this kind of formal occurrence can be constituted as a figure of the altered state. The relationship between cinema and photography will be particularly explored, starting with films such as Antonioni’s Blow Up and Bergman’s Persona. The hallucinatory effect will thus be discovered not as opposed to that of reality, but a dialectic will be constructed between the two.
Keywords: Still image; Photography; Hallucination; Antonioni; Bergman